Post-Traumatic Distress and Burnout Among Chinese School Teachers: The Mediating Role of Forgiveness - Wang, Yabing; Chung, Man Cheung; Fang, Siqi (Frontiers in Psychology, 2021)
Purpose Teachers' mental health is concerning due to high stress at work. Its association with job-related stressors has been well documented. Little is known; however, about how traumatic life events and trauma reactions might contribute to their psychological distress. This paper is to explore whether Posttraumatic Stress Disorder (PTSD) following past traumatic event would predict burnout and psychiatric co-morbidity among Chinese k-12 school teachers and whether this prediction would be mediated by forgiveness after controlling for work-related factors. Methods Two hundred and seventy-nine Chinese teachers (F=223, M=56) from primary and secondary schools completed demographic information, Posttraumatic Stress Disorder Checklist for DSM-5 (PCL-5), Heartland Forgiveness Scale (HFS), General Health Questionnaire-28 (GHQ-28), Maslach Burnout Inventory-Educator’s Survey (MBI-ES), and a series of measures assessing work-related factors. Results Structured equation modelling (SEM) showed that after controlling for work-related factors, PTSD following past trauma was positively associated with burnout and general psychological problems but negatively associated with levels of forgiveness. Forgiveness carried the impact of PTSD onto burnout rather than general psychological distress. Conclusion To conclude, regardless of the level of stress experienced from working in school, primary and secondary teachers with PTSD from past trauma found it more difficult forgiving which in turn could affect their levels of burnout.